Change with Confidence : Answers to the 50 Biggest Questions That Keep Change Leaders Up at Night. - Buckley, Phil (Wiley, 2013)
Complete, actionable answers to the fifty burning questions managers routinely ask about how to manage change successfully In this book a change management professional with nearly a quarter-century's experience arms change leaders with complete, actionable solutions the most challenging questions they are likely to face. Over the course of his career leading big change projects in major corporations in the US, UK and Canada, Phil Buckley has detected a pattern to what leaders typically don't know about managing change in their organizations. In Change with Confidence, he disti.